Implementasi Manajemen Masjid Dalam Membangun Keberlanjutan Dakwah Islam - Oki Prayogi (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2024)
This study aims to identify key elements in mosque management as a strategy to support the mosque's role as a holistic center for da'wah. This research employs a literature review method by analyzing literature related to mosque management, management functions (POAC), da'wah strategies, as well as challenges and opportunities in its implementation. Data sources include scientific articles, reference books, and official documents such as guidelines from the Indonesian Mosque Council. The analysis was conducted qualitatively through theme categorization, comparison of research findings, and synthesis of theories and findings to develop a conceptual framework. The results indicate that mosques can optimize their role through the implementation of three main pillars: Sustainable Facilities Management (SFM), the development of social and economic empowerment for congregants, and the integration of technology and innovation. Despite challenges such as resource limitations, lack of understanding of modern management, and congregation participation issues, this study found that innovative strategies, such as digitization, training for mosque administrators, and collaboration, can be effective solutions. In conclusion, structured mosque management not only supports sustainable da'wah but also positions the mosque as a center for social transformation relevant to contemporary challenges. This study's findings are expected to serve as practical guidance for mosque administrators and mosque-based empowerment policies.